A fé de Pedro e o Pedro da fé: Reflexões exegéticas sobre Mateus 16.18-19 - Portella, Rodrigo (Vox Scripturae - Revista Teológica Internacional, 2011)
The article aims, from a viewpoint of hermeneutics historical-philological propose an exegesis that is a contribution to the issue of dialogical biblical interpretation on the relationship between the apostle Peter and the institution of the papacy from the text of Matthew 16.18-19. The text presented here has been in the history of Christianity, a factor of contention between Catholics, Orthodox and Protestants as to the interpretation of the figure of the apostle Peter. Thus, this paper discusses the interpretation of the leadership of Peter from the base text of ecclesiastical controversy, in order to offer a vision that is either ecumenical effort and faithful to the text in its context and, as much as possible, to reveal the intention of the historical Jesus, reflected in the theology of the primitive community, about the role of Peter in the Church.
Keywords: biblical hermeneutic; old history; pope